THE ROLE OF NURSES AS WITNESSES IN MEDICAL MALPRACTICE CASES INVOLVING DOCTORS - soares, dominggos; Sukendar (Universitas Duta Bangsa Surakarta, 2023)
Nurses play a vital role in healthcare facilities, yet there are no clear regulations regarding their obligations and legal protection in malpractice cases involving doctors. This legal uncertainty creates professional dilemmas, particularly when providing objective testimony. This study explores the role of nurses as witnesses in such cases using a qualitative approach based on literature analysis. Nurses contribute to justice by offering testimony from direct observations and medical documentation. Their statements clarify medical actions, patient conditions, and potential procedural violations. Beyond legal obligations, nurses have a moral duty to disclose the truth without external pressure. Their testimony is crucial in ensuring ethical and professional healthcare services. To uphold this role effectively, nurses must understand their rights, obligations, and legal protections, allowing them to act with professionalism and integrity.